SOCIAL RESPONSIBILITY WITH SHARED VALUE CONSTITUTES COMPETITIVE ADVANTAGES IN PERUVIAN AND MEXICAN COMPANIES - Gutiérrez Huby, Ana María (2015)
This article aims to deepen and provide awareness of the social responsibility with shared value to those involved in the business area of Peru and Mexico. We propose to raise awareness about the development of responsible corporate management. Among the most significant findings we include: the incipient implementation of responsible practices despite the proliferation of information on the subject, the exercise of leadership in responsible practices with shared value is applied mainly in large companies, the existence of interest and predisposition towards implementing responsible practices by the SME, a growth in the interest in this trend by universities and corporate training centers, and finally the lack of support from governments implementing a regulation that imposes tax regulations unfavorable to business growth. A market consolidation of corporate social responsibility shared value is necessary in both countries; as well as the ability of society to respond to positive or negative actions of enterprises.